A Survey of the Level of Organizational Health and Political Behavior of Managers in the Ministry of Health of Fars Province: The Second-Order Confirmatory Factor Analysis Approach - Mohsen Jabolgha; Sanjar Salajeghe; Saeed Sayadi (Fasa University of Medical Sciences, 2020)
Background & Objective: The present study aimed to investigate the level of organizational health and political behavior of managers in the Ministry of Health of Fars Province using the second-order confirmatory factor analysis. The statistical population of the study consists of two groups. The first group includes experts in the theories of organizational health and political behavior of managers, which were used in the design of structures. The second group includes all employees of Fars University of Medical Sciences (1780 individuals) who are working in the University of Medical Sciences of this province. 315 individuals were selected using Cochran's formula as the study sample. Materials & Methods: The methodology of the present study is a descriptive survey and the data were collected using researcher-made questionnaires on organizational health and political behavior of managers which were prepared based on in-depth studies and content analysis Also, the validity and reliability of the data were confirmed. The data were analyzed using SPSS and Lisrel software. Result: After seeking the opinion of experts and finalizing the structures, the results showed that both organizational health and political behavior of managers were at an acceptable level, which was verified by a univariate t-test. The findings of the second-order confirmatory factor analysis test also indicated that the constructs of both variables are acceptable. Conclusion: It is necessary to consider the findings of this paper in management operations in order to enhance organizational performance.